Sonochemically-fabricated Ga@C-dots@Ga nanoparticle-aided neural growth. Issue 7 (30th January 2017) - Nissan, Ifat; Kumar, Vijay Bhooshan; Porat, Ze'ev; Makovec, Darko; Shefi, Orit; Gedanken, Aharon
Abstract : In this paper, we report the fabrication of an antibacterial material, Ga-doped C-dots on Ga nanoparticles (Ga@C-dots@Ga NPs), which is deposited on a glass substrate for neural growth. Abstract : In this paper, we report the fabrication of an antibacterial material, Ga-doped C-dots on Ga nanoparticles (Ga@C-dots@Ga NPs), which is deposited on a glass substrate for neural growth. A one-step sonochemical process is applied for the simultaneous fabrication and coating of Ga@C-dots@Ga NPs using PEG 400 and molten gallium. The physical and chemical characteristics of the synthesized materials were studied using scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDS), fluorescence analysis, dynamic light scattering (DLS) and other techniques. SH-SY5Y cells were plated on the substrates. The effect of the Ga@C-dots@Ga NPs on the development of neurites during the initiation and elongation growth phases was studied and compared with C-dots, Ga@C-dots and Ga NPs. Our research focuses on the influence of the physical and chemical properties of composites on neurite growth. We observed that cells grown on a Ga@C-dots@Ga-coated substrate exhibit a 97% increase in the number of branches originating from the soma. We found that surface modification and particle morphology play a significant role in the neural growth.